The Nail Penetration Behaviour of Carbon Nanotube Composite Electrodes for Energy Storage - Evangelos Koliolios; Daniel G. Mills; James J. C. Busfield; Wei Tan (Frontiers in Materials, 2021)
The high surface area, electrical and mechanical properties of carbon nanotube (CNT) composites has rendered them promising candidates for structural power composites. Nevertheless, it is important to understand their mechanical behaviour before they are applied in energy storage devices amid the safety concerns. This work explores the nail penetration behaviours of supercapacitor specimens consisting of CNT electrodes and pseudocapacitor specimens with carbon nanotube-polyaniline (CNT/PANI) electrodes. Specimens with and without electrolyte were tested. The dry cells without electrolyte follow a power law behaviour, while the wet cells with the electrolyte exhibit a piece-wise nonlinear relationship. The force, voltage and temperature of the supercapacitor were recorded during the nail penetration test. No temperature change or overheating was observed after short-circuit. Moreover, electrochemical testing is performed before and after the specimen penetration. The cyclic voltammetry shows the dramatic loss of capacitance, changing the cell behaviour from capacitor to resistor-like manner. Johnson-Cook model was used to predict the nail penetration behaviour. The coefficients of Johnson-Cook model are calibrated from the experimental load-displacement curves. The finite element model predictions are in a good agreement with the experimental results.